Ponte; Realness. Symbiotic parasitism in drag - Georgiev, Victor Geoergiev (University of the Witwatersrand, Johannesburg, 2023)
The intended investigation explores queer identity and the extent to which it can symbiotically co-inhabit an outdated structure to create social cohesion and integration resulting in a regeneration. Consisting of interventions exploring identity representation and familial programmes to create a sense of community. Research focuses on vulnerable communities present within Ponte (a structure containing aspects of familiarity to Ballroom spaces) and their synergy with the Ballroom community in Johannesburg. Through architectural processes engaging with space making and programming, aims value the creation of space. Encouraging educational models through social engagement which facilitate acceptance, sex, and gender expressions through a mutual occupation. Theories identified in queer spaces and Hertzburgers writings provide solutions through familiarity and atmospheres that allow for a symbiosis of community. Research outcomes indicate an adaptive re-use of Ponte through a reprogramming relating to investigations that highlight the buildings previous intentions as a vertical city.
This document is submitted in partial fulfilment to the degree: Master of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa, September 2023.
Keywords: Queer architecture; Ponte; Ballroom South Africa; Adaptive reuse skyscrapper; UCTD; SDG-5: Gender equality